2016
DOI: 10.1253/circj.cj-15-0617
|View full text |Cite
|
Sign up to set email alerts
|

Beta-Blockers and Fetal Growth Restriction in Pregnant Women With Cardiovascular Disease

Abstract: Background:The effects of β-adrenergic blockers on the fetus are not well understood. We analyzed the maternal and neonatal outcomes of β-adrenergic blocker treatment during pregnancy to identify the risk of fetal growth restriction (FGR). Methods and Results:We retrospectively reviewed 158 pregnancies in women with cardiovascular disease at a single center. Maternal and neonatal outcomes were analyzed in 3 categories: the carvedilol (α/β-adrenergic blocker; α/β group, n=13); β-adrenergic blocker (β group, n=4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 20 publications
2
52
0
2
Order By: Relevance
“…Other adverse effects of β-blockers include reduced umbilical blood flow,16hypoglycaemia and bradycardia, all of which may cause IUGR 12. In this study, premature birth and LBWI were observed and may be more strongly associated in the BB group than in the non-BB group, whereas β-blockers may not be associated with IUGR.…”
Section: Discussionmentioning
confidence: 48%
“…Other adverse effects of β-blockers include reduced umbilical blood flow,16hypoglycaemia and bradycardia, all of which may cause IUGR 12. In this study, premature birth and LBWI were observed and may be more strongly associated in the BB group than in the non-BB group, whereas β-blockers may not be associated with IUGR.…”
Section: Discussionmentioning
confidence: 48%
“…Beta blockers are frequently used to prevent aortic dilation during pregnancy in Marfan syndrome and other aortopathies (Lind and Wallenburg 2001;Meijboom et al 2005;Omnes et al 2013). Although atenolol has been studied the most at prevention of aortic dilation in Marfan syndrome, other beta blockers are preferred in pregnancy, as atenolol is more frequently associated with intrauterine growth restriction (Tanaka et al 2016).…”
Section: Vascular Concerns: Aortopathies Managementmentioning
confidence: 99%
“…Teratogenicity (see section 3.5.2, table 3.9) BB beyond 6 weeks of gestation may increase the risk of foetal growth restriction (110) Other treatment options RAI is absolutely contraindicated in pregnant women due to the possible risk of miscarriages, foetal thyroid ablation and birth defects.…”
Section: Adverse Effectsmentioning
confidence: 99%